2005
DOI: 10.1016/j.jmwh.2004.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students' Knowledge of Midwifery Practice After Didactic and Clinical Exposure

Abstract: Information concerning the student outcomes of interdisciplinary education is limited. The purpose of this study was to identify the knowledge of third-year medical students regarding the practice of certified nurse-midwives (CNMs). A 1-page survey instrument was developed and pretested. The instrument was administered as a pre-and posttest at the beginning and end of 7 Obstetrics and Gynecology rotations at 2 medical school clinical campuses of a large Midwestern medical school. Direct interaction with CNMs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Midwives often integrate the teaching of medical students and residents into their care on an informal basis 7 . The tangential or direct involvement of medical students and residents in midwifery care frequently takes place in teaching hospitals where there is a midwifery practice not formally appointed as medical faculty 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midwives often integrate the teaching of medical students and residents into their care on an informal basis 7 . The tangential or direct involvement of medical students and residents in midwifery care frequently takes place in teaching hospitals where there is a midwifery practice not formally appointed as medical faculty 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Midwives often integrate the teaching of medical students and residents into their care on an informal basis 7 . The tangential or direct involvement of medical students and residents in midwifery care frequently takes place in teaching hospitals where there is a midwifery practice not formally appointed as medical faculty 7 . In these settings, midwives may be the informal consultants and mentors to the residents and medical students, including them in the care of patients or advising them on clinical issues when consulted 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Themes from published literature regarding the role of midwives in medical student and resident education include: 1) teaching the midwifery model of care to learners; 2) creating collaborative, interdisciplinary teams; and 3) developing professionalism . As midwives have taken on formal academic medicine teaching roles, there has been recognition of their value as teachers, evaluators, and mentors by both medical students and residents who have reported positive clinical learning experiences . In evaluations, medical students have indicated that certified nurse‐midwives (CNMs) have the capacity to teach medical students .…”
Section: The Role Of Midwives In Medical Student and Resident Educationmentioning
confidence: 99%
“…10,11 In 2000, Metheny and Angelini 12 described an interdisciplinary educational model in which midwives had successfully participated in medical obstetric education since the early 1990s. Hanson et al 13 studied medical students' knowledge of midwifery practice after didactic and clinical exposure. In this particular study, midwives were recognized for their active teaching role.…”
Section: Literature Reviewmentioning
confidence: 99%